(untitled) (Nigerian Journal of Technology, 2021)
The rapid growth in the number of online services has lead to an increasing number of different identities managed by each user that makes people feel overloaded and suffer from password fatigue. This poses a serious problem and makes people unable to control and protect their digital identities against identity theft. As organizations grow and adds services such as ecommerce and global remote access of services, controlling who is accessing what kind of information is also becoming a difficult task. This research therefore, presents the development of a user identity management system for cybercrime control. The four stages of an identity management life cycle were developed using some mathematical tools. A two-factor authentication technique was used in developing the system, the traditional username and password was also included with biometric features for robustness. A simulation was run on the model for users ranging from 10 to 1000 using life wild dataset, and accuracy was found to be 98.01%. http://dx.doi.org/10.4314/njt.v40i1.17